2021
DOI: 10.1016/j.jpap.2021.100068
|View full text |Cite
|
Sign up to set email alerts
|

A systematic scoping review of ultraviolet C (UVC) light systems for SARS-CoV-2 inactivation

Abstract: A significant amount of epidemiological evidence has underlined that human-to-human transmission due to close contacts is considered the main pathway of transmission, however since the SARS-CoV-2 can also survive in aerosols, water, and surfaces, the development and implementation of effective decontamination strategies are urgently required. In this regard, ultraviolet germicidal irradiation (UVGI) using ultraviolet C (UVC) has been proposed to disinfect different environments and surfaces contaminated by SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…We have tested the approach with SARS‐COV‐2 as an example, due to its worldwide relevance. Experiments have found that the required dose to make inactive the SARS‐CoV‐2 virus is between 108 and 250J/m2 (Biasin et al, 2021; Derraik et al, 2020; Sabino et al, 2020; Sellera et al, 2021). In this work the applied dose is 500J/m2 to ensure a higher reduction.…”
Section: Control Architecture For Uv‐c Disinfectionmentioning
confidence: 99%
“…We have tested the approach with SARS‐COV‐2 as an example, due to its worldwide relevance. Experiments have found that the required dose to make inactive the SARS‐CoV‐2 virus is between 108 and 250J/m2 (Biasin et al, 2021; Derraik et al, 2020; Sabino et al, 2020; Sellera et al, 2021). In this work the applied dose is 500J/m2 to ensure a higher reduction.…”
Section: Control Architecture For Uv‐c Disinfectionmentioning
confidence: 99%
“…[14][15][16][17] The UVC range shows the strongest antiviral and antibacterial activity among the three applied UV wavelength ranges, including UVA (315-400 nm) and UVB (280-315 nm) ranges. 18 The available scientific literature shows that three UVC range subsets (i.e., 207-222 nm, 19,20 254 nm, 21,22 and 260-280 nm 23,24 ) are considered to be optimal for pathogen disinfection. A wavelength of 254 nm is the commonly used inactivation wavelength in most disinfection systems.…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which ultraviolet radiation may induce these side-effects is dependent on the wavelength of UV radiation, the dose of UV radiation and the susceptibility of the individual (7,21,22). Due to the potentially undesirable impact on human health, caution is, therefore, advised with regards to using UV-C devices in domestic and commercial settings (23). Currently, there is limited data that extends beyond a case-study approach to examine how and why risks of UV-C exposure may exist from a consumer perspective.…”
Section: Introductionmentioning
confidence: 99%